Diversion evaluations: a specialized forensic examination. (19th October 2017) - Barber‐Rioja, Virginia; Rotter, Merrill; Schombs, Faith
Abstract: Diversion programs screen justice‐involved individuals for the presence of psychiatric disorders, and after negotiations take place with attorneys and treatment providers, these programs link participants with community‐based treatment programs in lieu of incarceration. As the number of diversion programs, including mental health courts, continues to rapidly grow, so does the need for "diversion evaluations". Diversion evaluations are a type of forensic mental health assessment (FMHA) conducted to assist the courts in making decisions regarding diversion eligibility. As a result, they should follow the general principles of FMHA and the American Academy of Psychiatry and Law Practice Guideline for Forensic Assessment. Diversion evaluations also require application of specific areas of knowledge and experience, as court‐based diversion is a unique, therapeutically focused context that is purposefully non‐adversarial. The diversion evaluator is a role that combines objective decision‐making with clinical consultation. The purpose of this article is to apply generally accepted forensic report standards to diversion evaluations, with a particular focus on the unique issues of diversion‐specific forensic evaluations.